Fenomena Menarik Perkawinan Dibawah Umur Menjadi Trend Masa Kini di Bittuju Tapanuli Selatan - Rasyid, Arbanur; Siregar, Sawaluddin (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
This article examines the phenomenon of underage marriage in Bittuju, South Tapanuli. Many people who are still underage apply for marriage in the Religious Courts, especially because of the change in Law No. 1 of 1974 to Perma No. 5 of 2019. This research is descriptive qualitative, by conducting observations, interviews and document studies. The data analysis technique carried out by the researcher is a qualitative analysis by describing clearly and in depth the underage marriage. The results of this study conclude that underage marriages that occur in Bittuju, South Tapanuli are self-willed and factors of pregnancy outside marriage